2015
DOI: 10.1016/j.coldregions.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Snow as a driving factor of rock surface temperatures in steep rough rock walls

Abstract: Observations show that considerable amounts of snow can accumulate in steep, rough rock walls. The heterogeneously distributed snow cover significantly affects the surface energy balance and hence the thermal regime of the rock walls. To assess the small-scale variability of snow depth and rock temperatures in steep north and south facing rock walls, a spatially distributed multi-method approach is applied at Gemsstock, Switzerland, combining 35 continuous near-surface rock temperature measurements, high resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
92
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(112 citation statements)
references
References 41 publications
10
92
1
Order By: Relevance
“…In gently inclined, blocky terrain, effective ground surface insulation from cold atmospheric conditions was observed and modelled for snow depths exceeding 0.6 to 0.8 m (Hanson and Hoelzle, 2004;Keller and Gubler, 1993;Luetschg et al, 2008). In contrast, Haberkorn et al (2015a) found that snow depths exceeding 0.2 m were enough to have an insulating effect on steep, bare bedrock. Such amounts are likely to accumulate in steep, high rock walls with a certain degree of surface roughness.…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…In gently inclined, blocky terrain, effective ground surface insulation from cold atmospheric conditions was observed and modelled for snow depths exceeding 0.6 to 0.8 m (Hanson and Hoelzle, 2004;Keller and Gubler, 1993;Luetschg et al, 2008). In contrast, Haberkorn et al (2015a) found that snow depths exceeding 0.2 m were enough to have an insulating effect on steep, bare bedrock. Such amounts are likely to accumulate in steep, high rock walls with a certain degree of surface roughness.…”
mentioning
confidence: 66%
“…Such amounts are likely to accumulate in steep, high rock walls with a certain degree of surface roughness. Indeed, a warming effect of the snow cover on mean annual ground surface temperature (MAGST) was observed by Haberkorn et al (2015a) and Magnin et al (2015) in shaded rock walls, whilst in moderately inclined (45-70 • ) sun-exposed rock walls Hasler et al (2011) suggest a reduction of MAGST of up to 3 • C compared to estimates in near-vertical, compact rock due to snow persistence during the months with most intense radiation. Those observations emphasize the need to account for the strongly varying snow cover in thermal modelling of steep rock walls.…”
mentioning
confidence: 99%
See 3 more Smart Citations